Physician Burnout and the Americans with Disabilities Act - Lawson, Nicholas D. (The Hastings Center report, 2020)
The writer responds to the commentary “Physician Burnout Calls for Legal Intervention,” by Sharona Hoffman, in the November-December 2019 issue of the Hastings Center Report.